Combating corruption in a microfinance institution. Issue 4 (4th April 2017) - Azim, Mohammad I.; Sheng, Kuang; Barut, Meropy
Abstract : Purpose: Combatting corruption is an important social and commercial issue in most human societies. Many researchers have revealed how an effective anti-corruption practice can possibly minimise corruption in an organisation. However, studies focusing on organisations which are relatively successful in managing corruption at the employee level are relatively rare. On this note, this study aims to focus on Grameen Bank in particular, a Nobel-Prize-winning microfinance institute that was able to minimise its level of corruption among its employees in a country where corruption is the norm. Design/methodology/approach: This paper uses standard economic theory to explain the perceptions and behaviours of the employees of Grameen Bank who live and work in a highly corrupt socio-cultural environment. This paper used questionnaires to ascertain the perceptions of Grameen Bank employees' notions regarding corruption-combating behaviours. Interviews were also conducted among Grameen's board members, managers and officers to further explore the nature and effectiveness of this organisation's anti-corruption mechanisms. Findings: Corruption can never be entirely eradicated; however, it can be diminished and opportunities for corruption can be minimised. This paper found, through an analysis of employees' perceptions relating to governance and corruption in the Grameen Bank, that corruption exists, but there are systems in place to prevent it and to assist with staff morality. This research also uncovered a number of best practices in Grameen Bank's governance to minimise corrupt behaviours, which include, but are not limited to, strong monitoring, decentralisation of authority, review of decision-making process, high internal audit intensity, impersonal punishment, anti-corruption cultures and transparency. Originality/value: This study suggests that it is possible for organisations to resist corruption, especially microfinance institutions, even when they operate in a highly corrupt socio-cultural environment.